CLOSE PARENTAL ATTACHMENT AND MENTAL HEALTH FUNCTIONING IN UNIVERSITY STUDENTS: THE MEDIATING ROLE OF OPTIMISM - khan, Zarmina; Saleem, Sadia; Zahra, Sayyeda Taskeen; Aslam, Fatima (Journal of Pakistan Psychiatric Society, 2025)
To explore the mediating role of optimism between attachment styles and mental health functioning in university students of Lahore. STUDY DESIGN Cross-sectional study PLACE AND DURATION OF STUDY The study was conducted in Lahore in an 8-month period METHOD A total of 300 university students from private and government universities of Lahore were surveyed using the Adult Attachment Scale (AAS), Optimism Scale (OS) and Student Problem Checklist Scale (SPCL). Data were entered and analysed with the help of SPSS version 25. RESULTS The correlation analysis depicted a significant positive relationship between attachment (Close) and optimism, whereas there was a significant negative relationship between optimism and mental health functioning. Mediation analysis showed that optimism mediated the relationship between close attachment style and mental health functioning. CONCLUSION In terms of perceived close attachment, optimism played a protective role in the better mental health functioning of university students. KEYWORDS Attachment Styles, Optimism, Mental Health, Students